Analisis Putusan Eksekusi Jaminan Debitur Wanprestasi dalam Perjanjian Hutang Piutang (Studi Kasus Putusan Pengadilan Tinggi Nomor 238/Pdt.G/2020/Pt.Dki) - Rahmah, Salma Yustia; Djajaputera, Gunawan (Universitas Ekasakti, 2023)
The execution of collateral can be carried out when there is a court decision that takes into consideration whether there has been a breach of contract. This study employs a normative juridical approach as the basis for analyzing this legal issue. The research findings indicate that the debtor is legally entitled to execute the collateral concerning the breach of a debt agreement in the Decision of the High Court Number 238/Pdt.G/2020/PT.DKI. This is because both parties have a legally valid relationship to enter into a debt agreement, which was done by the plaintiff with the defendant I and II, with collateral in the form of a Certificate of Ownership for an Apartment Unit (SHMSRS) No. 3548/XXII/RIO DE JANEIRO, which has undergone the transfer process at the National Land Agency (BPN) in North Jakarta, registered in the name of the Defendant I, in this case, PT. Xiongji International Imp. & Exp. Group. The court decision to cancel the collateral seizure execution, which was previously determined as a result of the breach of contract by Defendant I in the Decision of the High Court Number 238/Pdt.G/2020/PT.DKI, is incorrect. This is because the petitioner of the collateral seizure has not paid the fees to the North Jakarta District Court until now. However, the judge ruled that Defendant I was at fault for the breach of contract, yet, on the other hand, the judge has canceled the collateral seizure execution against the collateral object guaranteed in the agreement.